2022
DOI: 10.1007/s00259-022-05835-4
|View full text |Cite
|
Sign up to set email alerts
|

Imaging PARP with [18F]rucaparib in pancreatic cancer models

Abstract: Purpose Rucaparib, an FDA-approved PARP inhibitor, is used as a single agent in maintenance therapy to provide promising treatment efficacy with an acceptable safety profile in various types of BRCA-mutated cancers. However, not all patients receive the same benefit from rucaparib-maintenance therapy. A predictive biomarker to help with patient selection for rucaparib treatment and predict clinical benefit is therefore warranted. With this aim, we developed [18F]rucaparib, an 18F-labelled isotopo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 39 publications
2
9
0
Order By: Relevance
“…Consistent with previously reported data [24], an increased concentration of radiotracer given to cancer cells resulted in increased cell uptake of radioactive material as shown in Fig. 3B.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Consistent with previously reported data [24], an increased concentration of radiotracer given to cancer cells resulted in increased cell uptake of radioactive material as shown in Fig. 3B.…”
Section: Discussionsupporting
confidence: 92%
“…Western blot revealed that expression of PARP-1 was higher in PSN-1 and FLO-1 cells than others, consistent with previously reported data [24], while expression of PARP-2 was higher in OE-33 and H1299 (Fig. 3G).…”
Section: Western Blot Analysissupporting
confidence: 92%
See 3 more Smart Citations